Pulmonary Mucormycosis secondary to Severe Acute Respiratory Illness due to Covid 19 Infection: A Case Report - Karthak, Ashish; Shrestha, Ashish; Gurung, Naresh; Bhusal, Yuvaraj; Lama, Rakesh; Rayamajhi, Sulav; Bhattarai, Sanjeet; Regmi, Asim; Ghimire, Anup; Khanal, Kishor; et al. (Nepalese Respiratory Journal, 2022)
Patients diagnosed and hospitalized with SARS COV-2 are managed with corticosteroids due to its known benefits for the prevention of airway inflammation secondary to acute respiratory distress syndrome seen commonly in viral pneumonia. However, these patients carry a high risk of developing secondary bacterial and fungal infection. We present a case of 60-year-old male with COVID-19 pneumonia. The patient was diagnosed with pulmonary mucormycosis 18 days following admission. The patient was treated with broad-spectrum antibiotics, remdesivir and corticosteroids along with antifungals including voriconazole and amphotericin B with no significant improvement. However, even after extensive medical management patient was eventually intubated and succumbed to its complications. Mucormycosis although an uncommon infection should be considered due to extensive use of glucocorticoid therapy and concurrent comorbidities present among COVID-19 patients.